Pengaruh Celebrity Endorse (Attractiveness, Trustworthiness, dan Expertise) terhadap Minat Beli pada Brand Erigo di Kota Surabaya - Muhammad Nur Fuady Mahardika; Siti Ning Farida (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to determine the effect of celebrity endorsement (attractiveness, trustworthiness, and expertise) on buying interest in the Erigo brand in the city of Surabaya. This research is a prospective consumer who wants Erigo products in the city of Surabaya. The number of samples in this study were 100 respondents. The sampling technique used was purposive sampling with the criteria of prospective consumers aged 12-30 years, potential consumers who wanted to have the Erigo brand, and domiciled in the Surabaya area. Data analysis technique using multiple linear regression test. The results of this study are the Attractiveness Variable (X1) partially has a significant effect on Erigo's buying interest (Y) in Surabaya. Furthermore, the Trustworthiness variable (X2) partially has a significant effect on Erigo's buying interest (Y) in Surabaya. Then, the Expertise Variable (X3) partially has a significant effect on Erigo's buying interest (Y) in Surabaya. And Attractiveness (X1), Trustworthiness (X2), and Expertise (X3) which are part of Celebrity endorse simultaneously significantly influence Erigo's buying interest (Y) in Surabaya. Keywords: Celebrity Endorsement; Buying Interest (Attractiveness, Trustworthiness, Expertise); Erigo